Portable Fire Pump To Handle Forest Fires and Densely Populated Urban Areas - Satria, Iman (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
A portable fire pump is an innovative fire extinguisher with high mobility because this tool can be carried by the user. This tool can answer the problem of fires that often occur in areas that are difficult to reach by fire extinguishers in general, such as in forests or densely populated urban areas. This portable fire pump can be operated by utilizing water pressure from a pump that is placed near a water source and then the pressure is added by this tool to reach hotspots. Based on testing, this tool is capable of spraying water as far as 10 meters with a height of 15 meters. In terms of ergonomics and the risk of muscle injury from the user, this tool has been tested using anthropometry methods, Rapid Upper Limb Assessment (RULA), and Recommended Weight Limit (RWL) with results that can be used by users without risking muscle injury